2002
DOI: 10.1046/j.1440-1754.2002.00044.x
|View full text |Cite
|
Sign up to set email alerts
|

Milk formulas in acute gastroenteritis and malnutrition: A randomized trial

Abstract: In these Aboriginal children with diarrhoea and growth failure, a low osmolality milk was associated with better outcomes and a partially hydrolysed formula with less improvement in mucosal recovery, suggesting that cow's milk protein intolerance is not contributing to greater diarrhoeal severity or enteropathy in Aboriginal children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 27 publications
0
32
0
1
Order By: Relevance
“…In Australian Aboriginal children who were underweight, osmotic diarrhoea was a common complication and linked to lactose intolerance and increased intestinal permeability leading to severe purging, hypokalaemia and metabolic acidosis [24]. In these children a low osmolarity, low lactose milk formula resulted in significantly better weight gain than either a low lactose or partially hydrolysed milk formula (both having higher osmolarities) [25]. A Zambian controlled trial of 4 weeks’ feeding with an amino acid-based elemental feed in severely malnourished or underweight children with persistent diarrhoea found better weight gains and greater increases in haemoglobin level than in children fed on cow’s milk or soya based formulas [26].…”
Section: Discussionmentioning
confidence: 99%
“…In Australian Aboriginal children who were underweight, osmotic diarrhoea was a common complication and linked to lactose intolerance and increased intestinal permeability leading to severe purging, hypokalaemia and metabolic acidosis [24]. In these children a low osmolarity, low lactose milk formula resulted in significantly better weight gain than either a low lactose or partially hydrolysed milk formula (both having higher osmolarities) [25]. A Zambian controlled trial of 4 weeks’ feeding with an amino acid-based elemental feed in severely malnourished or underweight children with persistent diarrhoea found better weight gains and greater increases in haemoglobin level than in children fed on cow’s milk or soya based formulas [26].…”
Section: Discussionmentioning
confidence: 99%
“…This could be indicative of an osmotic effect. Some studies have documented an increase in stool output/diarrhoea and a reduction in absorption of macronutrients in infants on feeds with a higher osmolality (Lifschitz & Carrazza, 1990; Kukuruzovic & Brewster, 2002) given at FS on day one. In contrast, another study (Khoshoo & Brown, 2002) investigating the gastric emptying of high‐ and low‐energy density whey‐based formulas in children with poor weight gain due to volume intolerance, found that an equal volume of the high‐energy density formula produced better weight gain without a change in tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…[58][59][60][61] Lactose-Free Formulas In developed countries, even in the case of acute gastroenteritis, enough lactose digestion and absorption are preserved so that low-lactose and lactose-free formulas have no clinical advantages compared with standard lactose-containing formulas except in severely undernourished children, in whom lactose-containing formu-las may worsen the diarrhea and lactose-free formulas may be advantageous. 62 Breastfed infants should be continued on human milk in all cases. 57 This has also been reviewed recently in the American Academy of Pediatrics' practice guideline for acute gastroenteritis.…”
Section: Managementmentioning
confidence: 99%